2014
DOI: 10.1016/j.jfludis.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Atypical central auditory speech-sound discrimination in children who stutter as indexed by the mismatch negativity

Abstract: a b s t r a c tPurpose: Recent theoretical conceptualizations suggest that disfluencies in stuttering may arise from several factors, one of them being atypical auditory processing. The main purpose of the present study was to investigate whether speech sound encoding and central auditory discrimination, are affected in children who stutter (CWS). Methods: Participants were 10 CWS, and 12 typically developing children with fluent speech (TDC). Event-related potentials (ERPs) for syllables and syllable changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 53 publications
4
31
0
7
Order By: Relevance
“…The interaction between the auditory aspects and the speech fluency has been demonstrated in the literature [17][18][19][20][21] , arousing thus the interest among researchers about the topic of stuttering and hearing.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The interaction between the auditory aspects and the speech fluency has been demonstrated in the literature [17][18][19][20][21] , arousing thus the interest among researchers about the topic of stuttering and hearing.…”
Section: Introductionmentioning
confidence: 98%
“…Studies in fluent individuals have shown that delayed auditory feedback (DAF) has caused difficulties in speech fluency [16][17][18][19][20][21][22] , and decrease in speech rate [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Children who stutter present central auditory discrimination impaired by less precise representation of speech sounds in relation to fluent children (8) . The results of an investigation with 27 children with stuttering and 28 controls suggest that the auditory-motor circuits and thalamic-cortical of the basal ganglia develop differently in children who stutter (16) .…”
Section: Introductionmentioning
confidence: 95%
“…Relevant information on the auditory aspects of speech fluency has been demonstrated in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) , increasing more and more the interest in this interface, stuttering and hearing, among researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation